Influence of hydroxypropyl methylcellulose and silica fume on stability, rheological properties, and printability of 3D printing foam concrete. (September 2021) - Liu, Chao; Wang, Xianggang; Chen, Yuning; Zhang, Chao; Ma, Lei; Deng, Zhicong; Chen, Chun; Zhang, Yamei; Pan, Jinlong; Banthia, Nemkumar
Abstract: Printability is a key parameter that affects the application of foam concrete to 3D printing. In this study, the hydroxypropyl methylcellulose (HPMC) and silica fume (SF) were doped into foam concrete as a viscosity modifier and thixotropic agent, and their effects on the stability, rheological properties, and printability of 3D printing foam concrete were investigated. Both HPMC and SF effectively reduced the volume bleeding rate of foam concrete, while HPMC was beneficial for stabilizing the foam, and SF increased the wet density of foam concrete. With the increase in the dosage of HPMC and SF and resting time, the static yield stress, dynamic yield stress, and plastic viscosity of foam concrete increased continuously. SF increased the static yield stress considerably, while HPMC affected the dynamic yield stress and plastic viscosity considerably. It is suggested to combine tanθ and stack height of the printed foam concrete together to evaluate the buildability of 3D printing foam concrete. The suitable ranges of static yield stress, dynamic yield stress and plastic viscosity for 3D printable foam concrete with a wet density from 1550 to 1850 kg/m 3 are 1113–1658 Pa, 66.4–230.1 Pa, and 2.08–3.71 Pa s, respectively. The compressive strength of the 3D printed foam concrete with dry density of 1815 kg/m 3 in the testing direction Z, Y, and X reached 19.9 MPa, 28.5 MPa and 24.6 MPa, respectively.